Influence of retinal NMDA receptor activity during autoimmune optic neuritis - Bojcevski, Jovana; Stojic, Aleksandar; Hoffmann, Dorit B.; Williams-Fairless, Sarah K.; Müller, Andreas; Diem, Ricarda; Fairless, Richard (Journal of neurochemistry, 2020)
Autoimmune optic neuritis (AON), a model of multiple sclerosis-associated optic neuritis, is accompanied by degeneration of retinal ganglion cells (RGCs) and optic nerve demyelination and axonal loss. In order to investigate the role of N-methyl-d-aspartate (NMDA) receptors in mediating RGC degeneration, upstream changes in the optic nerve actin cytoskeleton and associated deterioration in visual function, we induced AON in Brown Norway rats by immunization with myelin oligodendrocyte glycoprotein. Subsequently, visual acuity was assessed by recording visual evoked potentials and electroretinograms prior to extraction of optic nerves for western blot analysis and retinas for quantification of RGCs. As previously reported, in Brown Norway rats RGC degeneration is observed prior to onset of immune cell infiltration and demyelination of the optic nerves. However, within the optic nerve, destabilization of the actin cytoskeleton could be seen as indicated by an increase in the globular to filamentous actin ratio. Interestingly, these changes could be mimicked by intravitreal injection of glutamate, and similarly blocked by application of the NMDA receptor blocker MK-801, leading us to propose that prior to optic nerve lesion formation, NMDA receptor activation within the retina leads to retinal calcium accumulation, actin destabilization within the optic nerve as well as a deterioration of visual acuity during AON.
First published: 07 February 2020
Gesehen am 11.01.2022